Comparison of Information Collected by a Questionary with that in the Patient’s Hospital Record - YOUNG, D. W. (Methods of Information in Medicine, 1972)
Information about the medical history was collected from three sources: a) from a questionary, b) from an interview, and c) from the patient’s hospital record. The amount of information from these three sources was compared. The questionary, it was found, obtained about three times as many symptoms as were in the hospital record. Reasons for this are discussed, including the trivial nature of some of the symptoms found by the questionary. To obtain a better comparison, an attempt was made to divide the symptoms gathered by the questionary into significant and non-significant ones. On this basis, it is found that the questionary still collected twice as many symptoms as were in the patient’s hospital record.
Keywords: Hospital Record; Questionary